PENGARUH KARAKTERISTIK PEKERJAAN, DISIPLIN KERJA, DAN KOMUNIKASI INTERNAL TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KEPUASAN KERJA (STUDI PADA LPMP PROVINSI JAWA TENGAH) - Dista Aditya Putra, 12.52.02.0181; Setyowati, Widhy (Jurnal Mahasiswa Pasca Sarjana, 2015)
The performance of LPMP employees, especially the public servants, is not optimum and tends to decrease. This situation leads to poor working satisfaction and performances. This is a case study conducted at LPMP Provinsi Jawa Tengah. The purposes of the study are to identify the influence of job characteristics, discipline, and internal communication on the employeeâs performance. The mediating variable of this study is working satisfaction. Employing population technique, 125 public servants of LPMP are involved in the study. The instrument is examined through factor analysis, i.e. validity and reliability tests. To analyze the data the multiple linear regressions is used by employing determination coefficient model and F-test, and also conducting t-test to examine the hypothesis. The analysis reveals the following results: job characteristics has positive, but not significant influence on job satisfaction; discipline and internal communication influences positively and significantly towards job satisfaction;; job characteristics and job satisfaction affect on employeeâs performance positively and significantly; discipline and internal communication has positive, but not significant on employeeâs performance; job satisfaction and internal communication does not mediate job characteristics on employeeâs performance; job satisfaction mediates discipline on employeeâs performance. The most dominant variable influencing job satisfaction is discipline, while the most dominant variable affecting employeeâs performance is working satisfaction. Key words: job characteristics, discipline, internal communication, job satisfaction, employeeâs performance